Small ruminant marketing in southwest Nigeria - Francis, P.A. (Wiley, 1990)
Examines the influence of breed, sex, live-weight and time & place of sale on small ruminant prices in six southwest Nigerian markets. Assesses the relationship of prices between markets and the degree of integration between them. Includes a brief description of the structure of small-ruminant marketing in southwest Nigeria. Presents data on number of animals available for sale by breed and market, prices weights and price weight correlation coefficients, estimated parameters of linear and log-linear demand equations, values of tests of homogeneity & interactions of log-linear demand models with regard to sex, market location, & month of sale, and bivariate correlation coefficients of monthly prices per kg live-weight between markets.